Prevalence and onychoscopy features of benign longitudinal melanonychia in richly pigmented skin individuals - Ehiaghe L. Anaba; Obumneme E. Okoro; Babawale Arabambi (Journal of the Egyptian Women’s Dermatologic Society)
Background Benign longitudinal melanonychia (BLM) is not readily documented in richly pigmented skin individuals. Objective To determine the population-based prevalence of BLM and to document its onychoscopy and clinical features. Patients and methods This was a cross-sectional study of 1304 participants from October to December 2022 at the Lagos State University Teaching Hospital, Lagos, following ethical clearance. The finger and toe nails of the participants were examined for BLM. Onychoscopy was conducted on individuals who had BLM. Data were analyzed using SPSS version 25. Simple means and frequencies are presented. Results The prevalence of BLM was 30%, occurred in 50.6% of females and was more prevalent in individuals aged greater than 60 years. The colour of BLM was brown in 80.6%, regular width, uniform colouration and spacing in 100%. BLM mostly occurred on one digit and occurred more on the finger nails than the toe nails. The thumb and the index fingers of the hand, the big toe and the second toe nails were predominantly affected. Conclusion Benign longitudinal melanonychia has a high prevalence in richly pigmented skin individuals and it occurs more in the seventh decade of life. It affects females more and affects the finger nails more than the toe nails. A family history, onset after trauma or pregnancy are uncommon. Onychoscopy reveals a predominantly brown colouration, a width of less than 3 mm, regular lines, uniform colouration, regular spacing and a regular width.